Estimating the mechanism of farmers' effective participation in Chinese rural land consolidation. Issue 1 (23rd July 2018) - Wang, Wenxiong; Yu, Lihong; Zhou, Wei; Marcouiller, David W.; Luo, Bin
Abstract : Purpose: Effective farmer participation in the rural land consolidation process has become increasingly important because it improves results in rural land consolidation and land use efficiency. The purpose of this paper is to examine the mechanism of farmers' effective participation in Chinese rural land consolidation. Design/methodology/approach: The authors empirically assess farmers' effective participation in the rural land consolidation process in ten counties of China's Hubei province. Focusing on an effective decision-making model, the authors comprehensively evaluated farmer participation using surveys that incorporated an index system and analyzed survey results using a structural equation model to examine factors that influenced farmer's effective participation. Findings: The results of the study suggest that the correlations between farmers' effective participation and the impacting factors the authors proposed were particularly strong. In addition, participation ability, participation opportunity and participation incentive are strongly associated with effective farmer participation. Thus, the authors highlight that incentives should be provided to encourage farmers' effective participation in rural land consolidation. Research limitations/implications: Because of the chosen approach and the set of the research object, the geographic context of the empirical survey work was limited; furthermore, the authors only studied the influencing factors at the individual level, leaving the interaction effects between governmental factors and farmer individual factors inadequately explained. Originality/value: Despite those limitations, these results serve as an important reference for government agencies and stakeholder groups in rural land consolidation decision making.